2020
DOI: 10.1161/atvbaha.120.314318
|View full text |Cite
|
Sign up to set email alerts
|

Bmal1 Deletion in Myeloid Cells Attenuates Atherosclerotic Lesion Development and Restrains Abdominal Aortic Aneurysm Formation in Hyperlipidemic Mice

Abstract: Objective: Although the molecular components of circadian rhythms oscillate in discrete cellular components of the vasculature and many aspects of vascular function display diurnal variation, the cellular connections between the molecular clock and inflammatory cardiovascular diseases remain to be elucidated. Previously we have shown that pre- versus postnatal deletion of Bmal1 (brain and muscle aryl hydrocarbon receptor nuclear translocator-like 1), the nonredundant core clock gene has contrasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 30 publications
1
39
0
1
Order By: Relevance
“…Despite an increasing awareness of the hazards of circadian disruption, modern lifestyle is subject to frequent desynchronization due to shift working, artificial light, and transmeridian air flight. While the molecular clock may be adjusted by small molecules that target clock proteins ( Cho et al, 2012 ; Solt et al, 2012 ; Wallach and Kramer, 2015 ), we have found that inhibiting circadian rhythms may also mitigate circadian disorders ( Yang et al, 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite an increasing awareness of the hazards of circadian disruption, modern lifestyle is subject to frequent desynchronization due to shift working, artificial light, and transmeridian air flight. While the molecular clock may be adjusted by small molecules that target clock proteins ( Cho et al, 2012 ; Solt et al, 2012 ; Wallach and Kramer, 2015 ), we have found that inhibiting circadian rhythms may also mitigate circadian disorders ( Yang et al, 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…36 Deficiency of BMAL1 during the development stage or adulthood has different consequences on the atherosclerotic processes. 14,16 Thus, the specific peripheral clock roles of Cry1/Cry2 in BMDCs, independent of the whole-body central clock rhythm, require further study. Disruption of the core circadian machinery is not always detrimental to cardiovascular physiology.…”
Section: Discussionmentioning
confidence: 99%
“…37 BMAL1 deficiency in smooth muscle cells prevents experimental aortic aneurysm 38 and deletion of BMAL1 in myeloid cells provides protection from both atherogenesis and abdominal aortic aneurysm. 16 Mice with CLOCK deficiency also exhibited an attenuated inflammatory response with altered inhibin signaling. 39 We reasoned that individual circadian genes may have different roles in different tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systolic blood pressure was measured in conscious mice using a computerized noninvasive tail-cuff system as we previously described. 21 Briefly, mice were pre-trained for three consecutive days for adapting the environment and the whole procedure. Before recording, mice may have a rest for about 5 minutes until the animal remained comfortably and quietly in the holder.…”
Section: Blood Pressure Measurementmentioning
confidence: 99%